The Relationship of Earphone Use to the Occurrence of Noise-Related Hearing Loss in Students of the Faculty of Medicine, Universitas Prima Class of 2022 - Sri Salsabila; Cut Elvira Novita; Ferdinando Motuho Baeha (Jurnal Pendidikan Indonesia, 2025)
The widespread use of earphones among college students, especially with high volume and long duration, increases the risk of noise-induced hearing loss (NIHL). Global data show that adolescents and young adults are a vulnerable group, but there are still limited studies examining the relationship between earphone use patterns and audiometry results in medical students in Indonesia. This study aims to analyze the relationship between the use of earphones and noise-induced hearing loss in students of the Faculty of Medicine, Universitas Prima Indonesia. Using observational analytical approaches and cross-sectional designs, data were collected through questionnaires and audiometric examinations on 20 respondents. The results showed that there was a significant relationship between the duration of earphone use and hearing loss (p = 0.010), while the frequency of earphone use did not show a significant relationship (p = 0.543). These results provide important evidence regarding the impact of earphone use on students' hearing health. This research is expected to be the basis for educational institutions to develop educational programs regarding the safe use of earphones to prevent hearing loss.